Meta Analisis Tentang Dinamika Kepemimpinan Sekolah Dasar di Asia Tenggara - Hilmi, Nasywa; Fauziah, Fauziah; Shaleh, Shaleh (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research aims to determine the dynamics of human capital-based principal leadership in developing effective elementary schools based on Islamic law in Southeast Asia. This research uses a qualitative meta-analysis method with data originating from UNESCO data and the results of research that has been conducted and published online nationally and internationally for the period 2020-2023. Leadership dynamics is a process that continues to change and develop in leading an organization or team. Dynamic leaders are mentors who not only influence and develop the people they lead, but are also able to read and react to different individuals. School principals have an important role in educational mobility and improving the quality of school education in Southeast Asia. The findings that researchers obtained from these evaluative and relational techniques have important meaning for academics in the field of Islamic education.